Political perspectives of relationship networks to internationalization of firms in an emerging economy - Monticelli, Jefferson Marlon; de Vasconcellos, Silvio Luís; Garrido, Ivan Lapuente (Internext, 2017)
The neo-institutional theory has been used to explain inter-organizational networks related phenomena from the economic and sociological perspectives. The political perspective has not been often used to study institutional contexts of networks. We aim to analyze the decision-making of the formal institutions in the internationalization process of firms in an emerging economy from a political bias. For the empirical field of study, we considered the Brazilian wine industry. Starting from a case study with twenty-three interviews with representatives of wineries and entities of this industry, our paper furthers the understanding of how institutions influence the internationalization of firms in an emerging economy. Based on the political perspective of the neo-institutional theory, our study describes how institutions, mainly the government, can influence an industry. Government cannot afford resources to benefit or protect all the industries, as well as cannot provide incentives to all firms, and those that are supported will lose competitiveness. For the firms, the choices are based on trying to achieve economic advantages through political influences. For the institutions, the choices are based on political influences considering institutional strategies.